2018
DOI: 10.1007/s10067-018-4255-3
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II type 1 receptor gene polymorphism and serum angiotensin-converting enzyme level in Egyptian children with systemic lupus erythematosus

Abstract: Angiotensin II, the major effective molecule of the renin-angiotensin system, plays a vital role in the development of systemic lupus erythematosus (SLE). To study angiotensin II type 1 receptor (AT1R) gene polymorphism at (A1166C) in Egyptian children with SLE and its correlation with serum ACE level and SLE manifestations. AT1R gene polymorphism (A1166C) was done in 123 children with SLE in comparison to 100 healthy controls using polymerase chain reaction-based restriction fragment length polymorphism metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“… 11 , 12 , 13 , 14 , 15 , 16 RAS includes Angiotensin‐Converting Enzyme ( ACE ), the key effector peptide of RAS, converts angiotensin‐I to angiotensin‐II and splits bradykinin into inactive fragments. 11 The alteration of ACE enzyme activity was associated with the development of many diseases such as COVID, 17 , 18 hypertension, and cardiovascular diseases (CVDs), 19 , 20 renal pathology, 21 Alzheimer disease, 22 , 23 polycystic ovarian syndrome, 24 and cancers. 25…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 12 , 13 , 14 , 15 , 16 RAS includes Angiotensin‐Converting Enzyme ( ACE ), the key effector peptide of RAS, converts angiotensin‐I to angiotensin‐II and splits bradykinin into inactive fragments. 11 The alteration of ACE enzyme activity was associated with the development of many diseases such as COVID, 17 , 18 hypertension, and cardiovascular diseases (CVDs), 19 , 20 renal pathology, 21 Alzheimer disease, 22 , 23 polycystic ovarian syndrome, 24 and cancers. 25…”
Section: Introductionmentioning
confidence: 99%
“…The AT1R gene [92] and AT2R gene [93] polymorphisms might be considered as potential risk factors for children from Egypt with SLE [92,93]. Shoaib et al [92] hypothesized that the AT1R gene polymorphism observed in SLE patients reduces the regulatory effect of miRNA155 on AT1R gene expression, leading to high levels of AT1R. This, in turn, contributes to enhanced pro-inflammatory effects.…”
Section: Lupus Erythematosus (Le)mentioning
confidence: 99%
“…This, in turn, contributes to enhanced pro-inflammatory effects. In addition, elevated serum ACE levels in SLE patients stimulate the production of Ang II, which acts through the AT1Rs and intensifies the pro-inflammatory effects, increasing the susceptibility to SLE [92].…”
Section: Lupus Erythematosus (Le)mentioning
confidence: 99%
“…3 Regarding Egyptian children with SLE, many susceptibility genes were previously studied as Interleukin-17F rs763780 and rs2397084 5 and Angiotensin II type 1 receptor genes polymorphism. 6 In the present study, we focused on genes controlling two important cytokines in pathogenesis of SLE as Tumor necrosis factor-oe (TNF-oe) and interferon oe (INF-oe). Both cytokines were found to cross regulate each other.…”
Section: Introductionmentioning
confidence: 99%
“…3 Regarding Egyptian children with SLE, many susceptibility genes were previously studied as Interleukin-17F rs763780 and rs2397084 5 and Angiotensin II type 1 receptor genes polymorphism. 6…”
Section: Introductionmentioning
confidence: 99%